SUPPORT STRUCTURE FOR GEARSHIFT LEVER - YAMAMOTO, DAISUKE; SASAKI, NAOMASA (2013)
The disclosed support structure for a gearshift lever (4) includes: a rotary shaft (10) to be connected to the gearshift lever; a base plate (3) having support sections (12a, 12b) that rotatably support the respective ends of the rotary shaft so as to support the gearshift lever such that same can move to and fro; a restraining component (15) that is assembled to the base plate so as to come into contact with the rotary shaft; and a fixing section (17) that fixes the restraining component to the base plate. The base plate (3) has guide sections (16) that guide the assembling of the restraining component (15) to the base plate. The rotary shaft (10) includes a main projection (Pm) and auxiliary projections (Ps) that project in the axial direction of the rotary shaft from the end face (Sa) of one end (10d) of the opposite ends of the rotary shaft. The amount of projection of each auxiliary projection is smaller than the amount of projection of the main projection. By fixing the restraining component (15) such that same comes into contact with the main projection (Pm) of the rotary shaft, the movement of the rotary shaft in the axial direction thereof is restrained under the cooperation between the restraining component and the support sections.